RANCANG BANGUN APLIKASI MOBILE LEARNING BAHASA MINANGKABAU PADA SMARTPHONE BERBASIS ANDROID - Izzan Muhamad Urfan; Dedy Irfan; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
This application development is based on the problem of cost and the time required to learn minang language through non-formal education. Consideration of costs that required to follow the non-formal education can be an inhibiting factor that cause lack of the interest to participate in education through this way. Books about Minang language learning is not as much as English textbook and Mandarin. An alternative solution is to use mobile learning as a form of mobile application development on the android operating system. Although there are applications that can be downloaded for free, but some of these applications is restricted to some particular level in their use. The objective of this thesis was to design its Android app which is expected to facilitate the user in learning English and Indonesian Minang language and build a Mobile Learning app that can display essential materials and practical in Minang language learning.In developing this application is using the model development process Prototyping and Android-based Java programming language with the Integrated Development Environment (IDE) Eclipse Juno. The results of this final project is a Mobile Learning applications based on Android that features to display the basic material in Minang-English and Indonesian language learning that can help the user in case the foreigner to study minang language more easily, effectively and efficientl and to provide information about minang language learning basic level includes the basic vocabulary, conversation examples and number that is used in the Minang language. It is hoped that these applications can provide convenience for the user in learning the Minang language basic material, so that the user can learn anywhere and anytime and may increase the interest of users to learn Minang Language. Keyword : Mobile Learning, Minang Language, Java, Android.